2016
DOI: 10.1182/blood.v128.22.329.329
|View full text |Cite
|
Sign up to set email alerts
|

Targeting FVIII-Specific B Cells Using BAR-Transduced Regulatory T Cells

Abstract: Up to a third of hemophilia A (HA) patients receiving therapeutic FVIII develop neutralizing antibodies termed "inhibitors". Once inhibitors develop, clinical management of HA patients becomes extremely difficult. Thus, a rational solution would be to establish FVIII-specific immune tolerance to FVIII in high risk patients. To address this issue in a mouse model of human HA, we elected to use an antigen-specific regulatory T cell (Treg) approach. Analogous to the chimeric antigen receptor (CAR) strategy succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Our labs have approached this issue by expressing specific receptors (or antigen) in expanded polyclonal Tregs or CD8 T cells, based on the seminal work by Eshhar (76,77) and on clinical success of chimeric antigen receptor (CAR) T cells as reported by June and colleagues (78,79). Since these studies have recently been published (80)(81)(82)(83) and reviewed (52, 84), we will provide only a brief outline of these approaches to induce immune tolerance.…”
Section: Modulation Of Fviii Immunogenicitymentioning
confidence: 99%
See 3 more Smart Citations
“…Our labs have approached this issue by expressing specific receptors (or antigen) in expanded polyclonal Tregs or CD8 T cells, based on the seminal work by Eshhar (76,77) and on clinical success of chimeric antigen receptor (CAR) T cells as reported by June and colleagues (78,79). Since these studies have recently been published (80)(81)(82)(83) and reviewed (52, 84), we will provide only a brief outline of these approaches to induce immune tolerance.…”
Section: Modulation Of Fviii Immunogenicitymentioning
confidence: 99%
“…Starting with Tregs purified from healthy donors, our efforts to engineer specificity into polyclonal Tregs used retroviral transduction of specific T-cell receptors (TCR) (80) or CARs (scFv) (81), or even antigen (as B-cell Antibody Receptor = BAR) (83). In the first application, we cloned TCRs from FVIII reactive T-cell clones obtained from mild hemophilia patients (24).…”
Section: Modulation Of Fviii Immunogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Zhang et al 6 showed that BAR-expressing Tregs suppressed the response to FVIII in vivo when given prophylactically.…”
Section: Antigen-expressing Cd4 Tregs and Cytotoxic T Cellsmentioning
confidence: 99%